Impact of the Dual Antiplatelet Therapy Score on Clinical Outcomes in Acute Coronary Syndrome Patients Receiving P2Y12 Inhibitor Monotherapy - Huang, Sheng-Wei; Chen, Po-Wei; Feng, Wen-Han; Hsieh, I-Chang; Ho, Ming-Yun; Cheng, Chung-Wei; Yeh, Hung-I; Chen, Ching-Pei; Huang, Wei-Chun; Fang, Ching-Chang; Lin, Hui-Wen; Lin, Sheng-Hsiang; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The dual-antiplatelet therapy (DAPT) score is used to stratify ischemic and bleeding risk for antiplatelet therapy after percutaneous coronary intervention (PCI). This study assessed the association between DAPT score and clinical outcomes in acute coronary syndrome (ACS) patients who were treated with P2Y12 inhibitor monotherapy. Methods: From January 1st 2014 to December 31st 2018, 498 ACS patients with early aspirin discontinuation for various reasons and who received P2Y12 inhibitor monotherapy after PCI, were enrolled. The efficacy and safety between those with low (<2) and high DAPT scores (≥2) were compared during 12-months follow-up after PCI. Inverse probability of treatment weighting was used to balance the covariates between the two groups. The primary endpoint was a composite outcome of all-cause mortality, recurrent ACS or unplanned revascularization, and stroke within 12 months. The safety endpoint was major bleeding, defined as BARC 3 or 5 bleeding. Results: The primary composite endpoint occurred in 11.56% and 14.38% of the low and high DAPT groups, respectively. Although there was no significant difference in the primary composite endpoint between the two groups in the multivariate Cox proportional hazards models, the risk of recurrent ACS or unplanned revascularization was significantly higher in the high DAPT score group (adjusted hazard ratio 1.900, 95% confidence interval 1.095–3.295). The safety outcome for BARC 3 or 5 bleeding was similar between the two groups. Conclusions: Our results indicate that ACS patients receiving P2Y12 monotherapy with high DAPT scores had an increased risk of recurrent ACS or unplanned revascularization.